2017
DOI: 10.3389/fimmu.2017.01036
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Metabolite Butyrate Induces Expression of Th1-Associated Factors in CD4+ T Cells

Abstract: Short-chain fatty acids (SCFAs), which are generated by the bacterial fermentation of dietary fibers, promote expansion of regulatory T cells (Tregs). Potential therapeutic value of SCFAs has been recently highlighted in the experimental models of T cell-mediated autoimmunity and allergic inflammation. These studies suggest that physiological intestinal concentrations of SCFAs within the millimolar range are crucial for dampening inflammation-mediated processes. Here, we describe opposing effects of SCFAs on T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(175 citation statements)
references
References 31 publications
3
169
1
2
Order By: Relevance
“…Only a small portion of them pass into the circulation and exert anti‐inflammatory and metabolic effects under normal physiological conditions . Other studies have also reported that oral administration of high dose of SCFAs induced strong immune response in renal tissue . Our correlation analysis showed a strong negative correlation between blood propionate and all three major cecal SCFAs with BUN, suggesting their protective effect in CKD mice.…”
Section: Discussionsupporting
confidence: 69%
“…Only a small portion of them pass into the circulation and exert anti‐inflammatory and metabolic effects under normal physiological conditions . Other studies have also reported that oral administration of high dose of SCFAs induced strong immune response in renal tissue . Our correlation analysis showed a strong negative correlation between blood propionate and all three major cecal SCFAs with BUN, suggesting their protective effect in CKD mice.…”
Section: Discussionsupporting
confidence: 69%
“…In vitro studies further established the role of butyrate in regulation of forkhead transcription factor FOXP3 (a lineage specification factor). Butyrate works as an inhibitor of histone deacetylases (HDAC) and promotes acetylation of histone H3 at the promoter of the gene encoding FOXP3 (Zeng and Chi, 2015 ; Kespohl et al, 2017 ; Supplementary Figure S1 ). SCFAs also influence the development of dendritic cells and inflammatory cytokines, thereby regulating the intestinal macrophages (Chauvistré et al, 2014 ; Supplementary Figure S1 ).…”
Section: Roles Of Short Chain Fatty Acids (Scfas) Produced By Gut Micmentioning
confidence: 99%
“…While the anti-inflammatory capacity of butyrate and other SCFAs has been extensively investigated, novel studies have revealed that CD4 + effector T cells might also be a cellular target for SCFAs 11 14 . Therefore, it will be particularly interesting to better understand the molecular mechanisms underlying cell- and tissue-specific responsive immune cell subsets in order to develop and provide a safe SCFA-based therapy for patients with autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%